(untitled) (Asian Journal of Medical and Biological Research, 2024)
Bangladesh, with its extensive river network, vast coastlines, and rich maritime heritage, stands at the crossroads of a transformative Blue Economy. This comprehensive review explores the rich tapestry of Bangladesh’s maritime journey. Commencing with a historical lens, it traces the nation’s roots in fisheries, showcasing its transformation into a diversified and dynamic Blue Economy. The significance of this transition unfolds across the review, underscoring the sector’s contributions to GDP, employment, and food security, while candidly addressing challenges such as overfishing and environmental impact. This work not only chronicles historical milestones but distills valuable lessons from both successes and setbacks, offering a nuanced understanding of the economic resilience embedded in Bangladesh’s fisheries sector. Beyond a historical retrospective, the review navigates through the contemporary landscape, emphasizing diversification beyond fisheries. It illuminates economic opportunities in maritime trade, explores non-fish marine resources, and delves into the transformative role of aquaculture. The policy framework governing Bangladesh’s Blue Economy comes into focus, dissecting government strategies, legal landscapes, and international collaborations. The review also champions environmental sustainability, highlighting the impact of Blue Economy activities on marine ecosystems and advocating for conservation measures, thus positioning Bangladesh as a steward of its rich maritime heritage. Financial mechanisms and investments emerge as pivotal elements, shaping the trajectory of Blue Economy projects, as evidenced by case studies that weave success stories and lessons learned into the narrative. Concluding with a forward-looking perspective, the study identifies emerging trends, growth opportunities, and strategies to tackle challenges, offering a comprehensive roadmap for sustainable development. In weaving together economic vibrancy, environmental stewardship, and future aspirations, this review illuminates Bangladesh’s maritime odyssey as a beacon for the global Blue Economy community. Asian J. Med. Biol. Res. 2024, 10(1), 9-41